Anti-GAD65 Antibody-Associated Autoimmune Encephalitis With Predominant Cerebellar Involvement Following Toripalimab Treatment: A Case Report of a Novel irAE of Toripalimab - Zhou, Huanyu; Xie, Xiaoxi; Zhang, Tianyu; Yang, Menghan; Zhou, Dong; Yang, Tianhua (Frontiers in Immunology, 2022)
Toripalimab (Junshi Bioscience Co., Ltd) is a new immune checkpoint inhibitor (ICI) that targets programmed cell death protein 1 (PD-1) in various cancers, including metastatic melanoma. No neurological immune-related adverse events (n-irAEs) of toripalimab have been reported, except for neuromuscular involvement. We report a case of a 63-year-old woman who presented with severe vertigo, vomiting, nystagmus, cerebellar ataxia, and cognitive impairment after toripalimab treatment for metastatic melanoma. Compared with the concomitant cognitive dysfunction and a pathological reflex involving the cerebral cortex, the signs and symptoms of cerebellar involvement were much more prominent. Anti-glutamic acid decarboxylase 65 (anti-GAD65) antibody was positive in both serum and cerebrospinal fluid (CSF). After intravenous immunoglobulin (IVIG) and methylprednisolone (IVMP) administration, the symptoms of vertigo and vomiting resolved, with cognitive impairment and cerebellar ataxia remaining. This is the first report of autoimmune encephalitis (AIE) as an n-irAE of toripalimab.